Pengaruh Penempatan dan Kompensasi Terhadap Kinerja Karyawan Pada PT. Primavera International Jakarta - Reni Febrianti; Mia Amanda (Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
Human resources have an important role for the company, because human resources are a combination of energy, physical, ideas, talents, knowledge, creativity and skills needed to move the company. An employee's performance is an important start for the creation of company performance. The purpose of this study was to determine the effect of placement and compensation on employee performance at PT Primavera International Jakarta. This research method is descriptive quantitative approach method, with multiple linear regression analysis techniques. Hypothesis testing used the F test and t test. This study uses 80 respondents. From the results of the analysis, showing that the results of the F test / feasibility of the model, it was found that the significance value for the simultaneous influence of X1 and X2 on Y was 0,000 0.05 and the calculated F value was 7.297 F table 3.11 so that it could be concluded that H3 was accepted which means that there are simultaneously X1 and X2 influences on Y.Keywords : Placement, Compensation, Employee Performance.